RANCANG BANGUN APLIKASI PHP GENERATOR BERBASIS WEB - Anie Rose Irawati; Dwi Sakethi; Ayu Izaddarwazah (Jurnal Komputasi, 2015)
In this research was developed a web-based application PHP Generator. The development aims to produce an application which can minimize the time in making of web-based information systems. This application was built using PHP programming language integrated with MySQL database and supported by javascript and jQuery. The research method which is used in this research is action research and prototyping as its software development method. This application can generate php files to add, view, edit, delete, and search data that has been stored in the database,either the entire data of a table or only the filtered data. It can display the form input elements that user wants to be generated file such as textfields, textarea, password, radio button, select option, or checkbox. In addition, this application was also completed with data validation functions for file to be generated.